Pengaruh Adversity Quotient Terhadap Hasil Belajar Kimia Pada Mata Pelajaran Kimia Di Kota Lhokseumawe - Isna Rezkia Lukman; Fakhrah Fakhrah; Zahara Zahara; Najiha Sabrina; Ratna Unaida (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to determine the effect of the adversity quotient and students' cognitive learning outcomes in chemistry subjects by rank spearmen. This research is a quantitative study, with the school population in Lhokseumawe City including SMAN 1 Lhokseumawe, SMAN 5 Lhokseumawe, SMAN 6 Lhokseumawe, SMAN 7 Lhokseumawe with a sample of 413 students, the sampling technique in this study used cluster sampling. Data collection methods used are interviews, questionnaires, and documentation. Methods of data analysis using descriptive analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test, and spearmen rank analysis. Spearmen's rank analysis shows the effect of an adversity quotient of 0.000 <0.05, which means that there is an influence of an adversity quotient on students' cognitive learning outcomes in chemistry subjects with a coefficient of determination of 3.50%.